A new regional balance: Regional specialization and growth: An analysis of spatial divergence in Northern Europe - Andreas P. Cornett (European Regional Science Association (ERSA), 2015)
Changing pattern of global specialization and trade has affected the regional economic landscape in Europe significantly during the last decades, often even more than endogenous factors or policy measures. After a period of conversion, processes of diversion has reentered the scene, particularly along functional rather than administrative regional divisions. The main focus in this paper is on the Northern part of Europe to avoid the direct economic impacts of the European debt crisis. The purpose of the current paper is to investigate these patterns with special attention on rural regions, intermediate city regions, the vicinity of the large urban agglomerations and the metropolitan regions. The project is both explorative and explanatory, aiming at to detect and discuss how different types of functional regions are affected by changes in the international division of production, and to identify the global and national drivers behind the process. The empirical analysis is mainly based on the development of local employment, total as well as industry wise. The empirical study is designed as a 2 step analysis based on data from Eurostat for Northern European regions in the first step, and an in depth study of Denmark in the second step. The conceptual anchor of the study is mainly based on new economic growth theory and to a minor extent on concepts international trade. The central research questions are to identify theoretical and conceptual explanations and well as to provide empirical evidence based on data from Northern Europe. Who are the winners or losers in this polarization process, and what characterize the well performing regions compared to the declining regions. Danish evidence from previous studies points toward a mixed pattern. Central and economically well-structured city-region can maintain growth; more peripheral located city-regions face problems. In the longer run the fundamental shift in business and industry away form traditional manufacturing and service toward knowledge intensive service and products may become decisive for the success of these regions.
Keywords: R1; R11; 330; new pattern of specialization - structural change - new economic growth theory -